Effect of Implementing E-Samsat, Quality Service and Sanctions Taxation to Compliance Must Tax Motorized Vehicles (PKB) at the Gowa Regency Samsat Office - Masrullah Masrullah; Endang Winarsih; Awalin Syayidah Mar'ah Mp (Jurnal Riset Perpajakan: Amnesty, 2024)
This study aims to analyze the influence of e-tax system implementation, tax service quality, and tax sanctions on motor vehicle taxpayer compliance. Primary data for this research was obtained by distributing questionnaires to taxpayers registered at the Samsat Office in Gowa Regency. The study involved 100 respondents and employed a quantitative approach using the Multiple Linear Regression Analysis method, with SPSS version 25 as a data analysis tool. The results of the analysis indicate that the implementation of the e-tax system, the quality of tax services, and tax sanctions have a significant impact on taxpayer compliance. These findings highlight the importance of integrating digital systems, improving service quality, and enforcing effective sanctions to enhance compliance among motor vehicle taxpayers. By focusing on these factors, tax authorities can address compliance challenges and encourage taxpayers to fulfill their obligations efficiently.